Cloning: the debate in France and the international context. - Casini, M.; Di Pietro, M.L. (Medicina e Morale, 2003)
In the last January the French Senate - during the intense debate on the revision of the Bioethics Law of 1994 - has approved a law that forbids every form of cloning, both "reproductive" and "therapeutic". It concerns an important, but not yet definitive, result, because it is necessary the approval of the French National Assembly. This result, that deserves to be underlined, is countercurrent in comparison to the general favourable attitude to the "therapeutic" cloning and contrary to "reproductive" one. The French law is lined up with the indications of the European Parliament according to which "a new semantic strategy tries to weaken the moral meaning of the human cloning" since "there is not some difference between therapeutic and reproductive cloning. In the article the decision of the Senate is inserted in a double context: the biolaw debate in France as well as in the international panorama. The numerous reviewed documents put in evidence that, once more, the human embryo is the centre of the discussion: if the embryo is an object, he can be used for reaching the objectives of the "regenerative" medicine, but if he is a subject he cannot be exploited for any purpose. The principle of relationship, the principle of equality, the principle of solidarity, the principle of prudence are the indications that the modern conception of the law offers for saying that every human subject is always a juridical subject.